2015
DOI: 10.1111/ane.12522
|View full text |Cite
|
Sign up to set email alerts
|

The change of plasma pituitary adenylate cyclase-activating polypeptide levels after aneurysmal subarachnoid hemorrhage

Abstract: Objective -Elevated circulating pituitary adenylate cyclase-activating polypeptide (PACAP) levels have been demonstrated to be associated with clinical outcomes of severe traumatic brain injury. The current study aimed to confirm whether elevated plasma PACAP levels are predictive of clinical outcomes of aneurysmal subarachnoid hemorrhage (aSAH). Materials and methods -One hundred and eighteen aSAH patients and 118 controls were recruited. Plasma PACAP concentrations were determined using enzyme-linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…In addition, the mean age of aSAH patients in this study was about 15 years younger than that of most cases (35). Nevertheless, in eastern part of China, the mean age of aSAH patients reported in some articles (36)(37)(38) was similar to that in our study. This diversity in age may be derived from the differences of races and regions.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the mean age of aSAH patients in this study was about 15 years younger than that of most cases (35). Nevertheless, in eastern part of China, the mean age of aSAH patients reported in some articles (36)(37)(38) was similar to that in our study. This diversity in age may be derived from the differences of races and regions.…”
Section: Discussionsupporting
confidence: 84%
“…The authors suggested that PACAP could be a good prognostic predictor in hemorrhage patients and hypothesized that the elevated blood PACAP levels may refl ect an overproduction of PACAP as a pathological response to the loss of neural tissue in the CNS and it might be associated with the neuroprotective effects of the neuropeptide. Another recent study has confi rmed these fi ndings in aneurysmal subarachnoid hemorrhage [ 15 ]. These authors examined 118 hemorrhage patients and compared them to 118 controls.…”
Section: Acute Spontaneous Basal Ganglia Hemorrhagementioning
confidence: 85%
“…Hemorrhage patients had significantly elevated PACAP levels on admission and plasma PACAP levels were independently associated with clinical severity scores. The neuropeptide was identifi ed as an independent predictor of survival [ 15 ], suggesting that PACAP might be a potential prognostic biomarker of subarachnoid hemorrhage.…”
Section: Acute Spontaneous Basal Ganglia Hemorrhagementioning
confidence: 99%
“…Changes in serum PACAP levels have been described in nephrotic syndrome and in cardiomyopathies, where a decrease has been detected [48,49]. Regarding nervous system conditions, elevation has been found in acute aneurysmal subarachnoid hemorrhage [50], in acute spontaneous basal ganglia hemorrhage [51], in ictal phases of migraine [52][53][54], while decreases have been described in interictal phases of migraine [52,55] and in female post-traumatic stress syndrome patients [56]. CSF PACAP levels are decreased in Alzheimer's disease [39,40] and multiple sclerosis [57].…”
Section: General Overviewmentioning
confidence: 99%